THE EFFECT OF GLUT4 EXPRESSION IN HIPPOCAMPAL NEURONS TO SPATIAL MEMORY OF DIABETES-INDUCED RATTUS NOVERGICUS - Harahap, Herpan Syafii; Padauleng, Novrita; Lestari, Rizka Vidya; Nurhidayati, Nurhidayati; Wedayani, Anak Agung Ayu Niti; Sari, Putu Suwita; Muliyana, Hifdzil Haq; Laksmana, Ngakan Putu Proudy; Sahly, Aliza Raudatin (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Identification of appropriate biomarker involved in the pathophysiology of diabetes-associated cognitive decline in animal model is necessary. Glucose transporter 4 (GLUT4) is the component of insulin-dependent neuronal signaling pathway needed for maintaining cognitive function. It is highly expressed in hippocampal neurons.Objective: To investigate the effect of GLUT4 expression in hippocampal neurons on the spatial memory of diabetes-induced Rattus novergicus.Methods: This experimental study used 24 male Rattus novergicus divided into control groups terminated on day-0 (C0), 14 (C1) and 28 (C2) and diabetic groups terminated on day-0 (D0), 14 (D1) and 28 (D2). Diabetes was induced using streptozotocin injections intraperitoneally. Spatial memory (travel time) of rats was assessed on day-14 and 28. Brain tissue sampling was performed for assessment of GLUT4 expression using immunohistochemical methods. Significant differences in means of GLUT4 expression and travel time between groups on day-0, 14 and 28 as well as correlation between means of GLUT4 expression and travel time in D1 and D2 were analyzed statistically.Results: The mean of GLUT4 expression in diabetic group was significantly higher compared to control on day-14, but not on day-0 and 28. The immunohistochemical examination confirmed this results. There were no significant differences in mean of travel time between control and diabetic groups on day-14 and 28. There were no significant correlation between means of GLUT4 expression and travel time in diabetic groups on day-14 and 28.Conclusion: The GLUT4 expression of hippocampal neurons did not significantly affect spatial memory of diabetes-induced Rattus novergicus.